Enhancing Performance of Silicone Hydrogel Contact Lenses with Hydrophilic Polyphenolic Coatings - Paul Demian; Daichi Nagaya; Roeya Refaei; Kaoru Iwai; Daiki Hasegawa; Masaki Baba; Phillip B. Messersmith; Mouad Lamrani (Journal of Functional Biomaterials)
This study explores the application of a dopamine-assisted co-deposition strategy to modify the surface of daily disposable silicone hydrogel contact lenses. Aiming to enhance the hydrophilicity of these typically hydrophobic lenses, we developed an industry-friendly process using simple dip coating in aqueous solutions. By co-depositing tannic acid, dopamine and chitosan derivative and employing periodate oxidation, we achieved a rapid and efficient coating process. High-molecular-weight branched polyethylene imine was introduced to promote surface reactions. The resulting lenses exhibited extreme hydrophilicity and lipid repellency without compromising their intrinsic properties or causing cytotoxicity. While the coating demonstrated partial antimicrobial activity against Gram-positive Staphylococcus aureus, it offers a foundation for the further development of broad-spectrum antimicrobial coatings. This versatile and efficient process, capable of transforming hydrophobic contact lenses into hydrophilic ones in just 15 min, shows significant potential for improving comfort and performance in daily disposable contact lenses.